Analysis and profitability assessment of Polish construction companies threatened with bankruptcy - Tomasz Maślanka (e-Finanse: Financial Internet Quarterly, 2017)
This paper presents analysis of profitability indicators of Polish construction companies threatened with bankruptcy compared to analogous indicators obtained by Polish construction entities as a whole. The analysis concerns companies generating positive and negative financial results (both EBIT and net financial results). Moreover, the operating profitability ratio, return on sales, and return on total assets ratios have been verified. The analyses have been conducted using financial reports of Polish construction companies which went bankrupt in 2013, as well as financial data of construction sector participants as a whole.
Keywords: G32; G33; 330; construction companies; profitability; bankruptcy